Diffuse non-aneurysmal SAH in spontaneous intracranial hypotension: Sequela of ventral CSF leak?. (May 2016) - Schievink, Wouter I; Maya, M Marcel
Background: Spontaneous intracranial hypotension due to a spinal cerebrospinal fluid (CSF) leak has become a well-recognized cause of headaches. Recently, various unusual neurological syndromes have been described in such patients with chronic ventral CSF leaks, including superficial siderosis and an amyotrophic lateral sclerosis-like syndrome. The authors now report two patients with spontaneous intracranial hypotension due to a chronic ventral CSF leak who suffered a diffuse non-aneurysmal subarachnoid hemorrhage (SAH). Description of cases: A 62-year-old woman underwent uneventful microsurgical repair of a ventral thoracic CSF leak that had been present for 13 years. Seventeen months after surgery, she was found unresponsive and CT showed a diffuse intracranial SAH. Cerebral angiography and spine and brain MRI did not reveal a source of the SAH. A 73-year-old woman was found unresponsive and CT showed a diffuse intracranial SAH. Cerebral angiography and brain MRI did not reveal a source of the SAH, although superficial siderosis was detected. Spine MRI showed a ventral thoracic CSF leak that by history had been present for 41 years. She underwent uneventful microsurgical repair of the CSF leak. Discussion: The authors suggest that patients with a ventral spinal CSF leak of long duration may be at risk of diffuse non-aneurysmal SAH.